HUBUNGAN DIABETES MELITUS DENGAN KEJADIAN MORTALITAS PADA PASIEN TERKONFIRMASI COVID-19 TAHUN 2020: SYSTEMATIC REVIEW - Ahda Faza Hunafa (2020)
COVID-19 is a respiratory disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Diabetes Mellitus (DM) is suspected as one of the causes that intensify the number of death of the COVID-19 patients. The literatures for DM in COVID-19 have always been updated as the disease swiftly spreading. This study aims to know the relation between DM and the mortality of confirmed patients of COVID-19 in 2020 using systematic review method. Journal searches are conducted from April to July 8th 2020 in publication literature centre with keywords "COVID-19" and "Glycaemic Control" or "Diabetes Control" and "Mortality" reported in Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P). Critical appraisal is made based on National Heart Lung and Blood Institute and the Research Triangle Institute International. The data are collected from eight journals that involved the research criteria (controlled diabetes and not controlled diabetes). This study has strongly proved that the mortality cases of confirmed COVID-19 are higher ini patients with DM as comorbid. Uncontrolled DM group has the higher percentage of mortality cases of 11% with a Risk Ratio (RR) of 2.56.